Survey of ICT and Education in Africa : Swaziland Country Report - Isaacs, Shafika (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev)-supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Swaziland is a small, deeply impoverished, drought-stricken country with a weak ICT infrastructure. The Swazi government introduced a draft national ICT policy in 2006 and the country has a very small number of ICT for education program under way of which the computer education trust and various program at the university of Swaziland are the most known.